The Great Reimagining: Public Art, Urban Space and the Symbolic Landscapes of a ‘New’ Northern Ireland (Bree T. Hocking: Berghahn, 2015) - McClelland, Andrew (Irish Journal of Arts Management and Cultural Policy, 2017)
A review of The Great Reimagining: Public Art, Urban Space and the Symbolic Landscapes of a ‘New’ Northern Ireland is written by Bree T. Hocking. The Great Reimagining: Public Art, Urban Space and the Symbolic Landscapes of a ‘New’ Northern Ireland is written by Bree T. Hocking, a Research Associate at the Open University with a background in exploring the intersection of art, spatial politics and society. This book critically investigates the global and local processes shaping public spaces in the two largest cities of ‘post-conflict’ Northern Ireland: Belfast and Derry. A particular emphasis is placed on interrogating selected state-financed public art commissions, questioning their intended impact, the sometimes contested and unforeseen community responses, and the insights derived as to the vision of citizenship the State is seeking to engender in the ‘new symbolic landscapes’ of Northern Ireland (p. 4). In essence, the study explores the dissonance and contradictions that typically manifest in the spatial restructuring of urban space, particularly where public art is mobilised by policymakers and funding bodies as a means of promoting local reconciliation and shared space while simultaneously calibrated to attract global investment capital and ‘consumer-tourists’. To this end, the author posits a conceptual framework for the analysis of official discourses shaping such ‘transitional space’ and asserts its wider applicability to other post-conflict and post-industrial societies.